Alkali-activated cement-based binder mortars containing phase change materials (PCMs): mechanical properties and cost analysis - Kheradmand, Mohammad (2020)
Energy efficiency is not only the most cost-effective way to reduce carbon dioxide emissions but also a way to improve competitiveness and create employment. EU aims to achieve nearly zero-energy (public) building (NZEB) by the end of 2018 (2020 for private buildings). This very ambitious target would be more easily fulfilled if high-performance thermal materials like phase change materials-PCMs are to be used. This paper reports experimental results on the properties of fly ash-based alkali-activated binder-AACB mortars in which a minor percentage of aggregates were replaced by PCMs. These include compression strength, at normal temperature and also at high temperatures, flexural strength, density, water absorption, unrestrained shrinkage as well as cost analysis. Several AACB mixtures showed an increase in compressive strength after being exposed to high temperatures. Since PCMs are made of flammable materials and AACB mortars show a much higher stability at high temperature than Portland cement-based mortars this means that AACB mortars are more suitable for PCM incorporation. This is a very important feature because flammable insulation materials were reported to be the cause of the recent Grenfell Tower fire tragedy that made 71 victims.